Preparation method of high-elasticity wear-resistant fabric

By twisting composite elastic fibers with nylon 66 filaments to form warp yarns, and combining them with a three-dimensional interwoven structure and abrasion-resistant coating, the compatibility problem of abrasion resistance and elasticity in elastic fabrics has been solved, realizing the preparation of highly elastic abrasion-resistant fabrics suitable for high-intensity outdoor sports and high-frequency industrial operations.

CN121344936APending Publication Date: 2026-01-16NANTONG WEIBASITE TEXTILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511836464.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-08
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing elastic fabrics have a trade-off between abrasion resistance and elasticity. In particular, their performance degrades rapidly under high temperature, high humidity, and frequent friction environments, making it difficult to meet the long-term use requirements of high-intensity outdoor sports and high-frequency industrial operations.

Method used

The fabric is made by twisting composite elastic fibers and nylon 66 filaments together to form warp yarns, and forming a 'plum blossom' locking structure through a three-dimensional cross-knitting process. A wear-resistant elastic coating is formed on the fabric surface that is tightly bonded to the fibers. The wear resistance and elasticity of the fabric are enhanced by the co-spinning of polyether ester, amino graphene and UHMWPE microfibers and the silicon carbide@graphene core-shell nanoparticle composite coating.

Benefits of technology

It achieves a synergistic improvement in abrasion resistance and elasticity of highly elastic fabrics. When stretched, the coils expand and release, and when rebounding, they quickly return to their original position. The dense distribution of interlacing points disperses frictional stress and avoids localized wear. The coating is tightly bonded to the fibers to maintain breathability and elasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121344936A_ABST
    Figure CN121344936A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-elasticity wear-resistant fabric, and relates to the technical field of textile fabric preparation, the preparation method comprises the following steps: carrying out melt blending spinning to obtain composite elastic fibers, doubling and twisting the composite elastic fibers and chinlon 66 filaments to form warp yarns, and taking UHMWPE filaments as core yarns, the preparation method comprises the following steps: taking a polyurethane urea elastomer and silicon carbide and graphene core-shell nanoparticles as raw materials, taking composite elastic fibers as fasciated yarns for wrapping to form weft yarns, weaving by a three-dimensional interlacing weave process of the warp yarns and the weft yarns, forming a quincunx locking structure by interweaving points, compounding the polyurethane urea elastomer and the silicon carbide and graphene core-shell nanoparticles to form a coating precursor solution, and immersing the rough fabric blank into the coating precursor solution; the composite elastic fiber has both high elasticity and basic wear resistance, the three-dimensional interlaced weave process can further enhance the synergy of the elasticity and wear resistance of the fabric, a coil is stretched to release elasticity when the quincunx locking structure is stretched, the coil is quickly reset when the quincunx locking structure rebounds, and the wear resistance of the fabric is improved. The coating precursor solution can form a wear-resistant elastic coating which is tightly combined with fibers and structures on the surface of the fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of textile fabric preparation technology, and in particular to a method for preparing a highly elastic and abrasion-resistant fabric. Background Technology

[0002] Elastic fabrics are widely used in various scenarios due to their excellent fit and freedom of movement. However, existing elastic fabrics generally suffer from the core problem of "equality and abrasion resistance being mutually exclusive." Fabrics with spandex as the elastic component can achieve an elastic recovery rate of over 90%, but spandex fibers have low surface hardness and poor abrasion resistance, making them prone to breakage, pilling, and short service life after repeated stretching and friction. Fabrics with ultra-high molecular weight polyethylene (UHMWPE) and nylon 66 as abrasion-resistant components have excellent abrasion resistance, but their elastic recovery rate is usually below 70%, resulting in poor fit and inability to meet the demands of dynamic movement.

[0003] Current technologies addressing these issues often employ blending elastic and abrasion-resistant fibers or applying an abrasion-resistant coating. However, blended fabrics suffer from poor compatibility between the two fibers, leading to delamination. Coated fabrics, on the other hand, experience coating peeling, affecting breathability and elasticity. In extreme environments (such as high temperature, high humidity, and frequent friction), the fabric's elasticity deteriorates rapidly, and its abrasion resistance drops significantly, making it unsuitable for long-term use in scenarios such as high-intensity outdoor sports and high-frequency industrial operations. Therefore, this invention proposes a method for preparing a highly elastic abrasion-resistant fabric to solve these problems. Summary of the Invention

[0004] To address the aforementioned issues, this invention proposes a method for preparing a highly elastic and abrasion-resistant fabric. The composite elastic fiber combines high elasticity with basic abrasion resistance. The three-dimensional interlacing process further enhances the synergy between the fabric's elasticity and abrasion resistance. The "plum blossom" locking structure allows the coils to stretch and release elasticity during stretching and quickly reset during rebound. The coating precursor solution can form an abrasion-resistant elastic coating on the fabric surface that is tightly bonded to the fibers and structure.

[0005] To achieve the objectives of this invention, the invention is implemented through the following technical solutions: A method for preparing a highly elastic abrasion-resistant fabric includes the following steps: Step 1: The composite elastic fiber is obtained by melt blending and spinning polyether ester chips, amino-based graphene, UHMWPE microfibers, and maleic anhydride-grafted polyolefin compatibilizer. Step 2: Twist the composite elastic fiber and nylon 66 filament together in a ratio of (6-7):(3-4) to form a twisted structure as the warp yarn; Step 3: Use UHMWPE filament as the core yarn and composite elastic fiber as the wrapping yarn to wrap the yarn, forming a core-spun structure as the weft yarn; Step 4: The warp and weft yarns are woven using a three-dimensional interlacing weave process. During the weaving process, the interlacing points of the warp and weft yarns are controlled to form a "plum blossom" locking structure to obtain the fabric rough. Step 5: Polyurethane urea elastomer is combined with silicon carbide@graphene core-shell nanoparticles to form a coating precursor solution. The fabric blank is immersed in the coating precursor solution, pre-baked and cured in situ, so that the coating precursor solution forms a network cross-linked coating with a thickness of 5-10μm on the surface of the fabric blank, and a highly elastic and wear-resistant fabric is obtained.

[0006] A further improvement is that: in the composite elastic fiber of step one, the proportion of amino-graphene is 2-5wt%, the proportion of UHMWPE microfiber is 5-10wt%, the proportion of compatibilizer is 3-5wt%, and the remainder is polyether ester chips. The UHMWPE microfiber has a diameter of 50-100nm and a length of 1-3μm.

[0007] A further improvement is made in the following step: In step one, when polyether ester chips, amino-based graphene, UHMWPE microfibers, and maleic anhydride-grafted polyolefin compatibilizer are melt-blended and spun, they are melt-blended at 220-240℃ using a twin-screw extruder, extruded and granulated to obtain a composite masterbatch. The composite masterbatch is then fed into a spinning machine with a spinneret orifice diameter of 0.1-0.2 mm, a spinning temperature of 230-250℃, a cooling air velocity of 0.8-1.2 m / s, and a draw ratio of 3-4 times to obtain composite elastic fibers.

[0008] A further improvement is made in step two, where the twist is controlled to be 800-1000 twists / meter when the composite elastic fiber and nylon 66 filament are twisted together.

[0009] A further improvement is made in step three, where UHMWPE filament is used as the core yarn and composite elastic fiber is used as the wrapping yarn, and the wrapping twist is 600-800 twists / meter.

[0010] A further improvement is made in the following: when the warp and weft yarns are woven using a three-dimensional interlacing weaving process in step four, the warp yarn density is 280-320 yarns / 10cm and the weft yarn density is 230-270 yarns / 10cm.

[0011] A further improvement is that the density of the "plum blossom" locking structure formed by the interlacing points of the warp and weft yarns in the fabric rough in step four is 1.5-2 times that of the plain weave.

[0012] A further improvement is that the core diameter of the silicon carbide@graphene core-shell nanoparticles in step five is 50-100 nm, and the shell thickness is 10-20 nm.

[0013] A further improvement is made in the following step: When the polyurethane urea elastomer and silicon carbide@graphene core-shell nanoparticles are combined to form the coating precursor solution in step five, the silicon carbide@graphene core-shell nanoparticles are first prepared into a dispersion. Then, the polyurethane urea elastomer is transferred to a constant temperature reactor and the temperature is maintained at 40-45℃. The stirring is started at a speed of 500-700 r / min. The dispersion is slowly added in three portions, and the stirring speed is increased and stirred for 20 min after each addition. Then, a polycarboxylate dispersant is added and stirring continues. Finally, a polyether-modified polysiloxane leveling agent is added and stirring continues for 30 min. The viscosity of the system is adjusted to 1000-1200 mPa·s, and an ethanol / deionized water mixed solvent is added to control the solid content of the precursor to 12%-14%, thus obtaining the coating precursor solution.

[0014] The further improvement is that: in step five, after the fabric blank is immersed in the coating precursor solution, the pre-baking temperature is 70-90℃, the pre-baking time is 8-12min, the in-situ curing temperature is 120-140℃, and the in-situ curing time is 20-30min.

[0015] The beneficial effects of this invention are as follows: This invention produces composite elastic fibers that combine high elasticity and basic wear resistance by using polyether ester as a base material and preparing them through graphene grafting modification and UHMWPE microfiber blending and spinning. Aminated graphene is grafted onto the polyether ester molecular chain, and the graphene sheets are covalently bonded to the polyether ester, which solves the compatibility problem between graphene and polymer. Furthermore, the high hardness and thermal conductivity of graphene can be used to improve the surface wear resistance and thermal stability of the composite elastic fibers. During the spinning process, UHMWPE microfibers can form a rigid support skeleton, which does not affect the elastic recovery of polyether ester and can disperse frictional stress, avoiding excessive local wear of the composite elastic fibers.

[0016] This invention uses composite elastic fiber and nylon 66 filament twisted together as warp yarn, and UHMWPE filament as core yarn and composite elastic fiber as wrapping yarn as weft yarn. The warp and weft yarns are woven using a three-dimensional interlacing structure, and the interlacing points of the warp and weft yarns are controlled to form a "plum blossom" locking structure, which can further enhance the synergy between the elasticity and abrasion resistance of the fabric. When stretched, the coils of the "plum blossom" locking structure release elasticity, and when rebounded, the coils quickly return to their original position. At the same time, the dense distribution of interlacing points can disperse external frictional forces and avoid local wear. This invention forms a coating precursor solution by combining polyurethane urea elastomer with silicon carbide@graphene core-shell nanoparticles. The fabric blank is then immersed in the coating precursor solution, pre-baked, and cured in situ. This process forms a wear-resistant elastic coating on the fabric surface that is tightly bonded to the fibers and structure, thereby achieving a secondary enhancement of elasticity and wear resistance. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the method flow of the present invention. Detailed Implementation

[0018] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.

[0019] according to Figure 1 As shown in the figure, this embodiment proposes a method for preparing a highly elastic abrasion-resistant fabric, including the following steps: Step 1: A composite elastic fiber is obtained by melt blending and spinning polyether ester chips, aminated graphene, UHMWPE microfibers, and maleic anhydride-grafted polyolefin compatibilizer. Specifically, the composite elastic fiber contains 4 wt% aminated graphene, 8 wt% UHMWPE microfibers, 4 wt% compatibilizer, and the remainder is polyether ester chips. The UHMWPE microfibers have a diameter of 580 nm and a length of 2 μm. During melt blending and spinning, the fibers are melt-blended at 230 °C using a twin-screw extruder, extruded and granulated to obtain a composite masterbatch. The composite masterbatch is then fed into a spinning machine with a spinneret orifice diameter of 0.15 mm, a spinning temperature of 240 °C, a cooling air velocity of 1.0 m / s, and a draw ratio of 3 times to obtain the composite elastic fiber.

[0020] Step 2: Twist the composite elastic fiber and nylon 66 filament in a 6:4 ratio, with the twist controlled at 900 twists / meter, to form a twisted structure as the warp yarn; in this step, the composite elastic fiber provides core elasticity, while the nylon 66 filament enhances the warp abrasion resistance and tensile deformation resistance.

[0021] Step 3: Using UHMWPE filament as the core yarn and composite elastic fiber as the wrapping yarn, the yarn is wrapped with a twist of 600 twists / meter to form a core-spun structure as the weft yarn. In this step, UHMWPE filament has ultra-high abrasion resistance. Through the wrapping effect of composite elastic fiber, the core yarn slippage is prevented, thus ensuring the elasticity of the fabric.

[0022] Step 4: The warp and weft yarns are woven using a three-dimensional interlacing structure on a rapier loom at a speed of 300 r / min. The warp density is 280-320 yarns / 10cm, and the weft density is 230-270 yarns / 10cm. During the weaving process, the interlacing points of the warp and weft yarns are controlled to form a "plum blossom" locking structure. The density of the "plum blossom" locking structure is 1.5-2 times that of the plain weave structure, resulting in a rough fabric. In this step, the loops expand and release elasticity during stretching, and quickly return to their original position during rebound, which greatly improves the abrasion resistance of the fabric compared to traditional plain weave fabrics, while maintaining an elastic recovery rate of ≥93%. In this step, during the weaving of the "plum blossom" locking structure, the interlacing of warp and weft yarns follows a "3 up, 2 down" cycle, meaning each warp yarn successively crosses 3 weft yarns and sinks through 2 weft yarns, forming an interlacing trajectory similar to plum blossom petals. At the interlacing points of the warp and weft yarns, they intertwine and wrap around each other (wrapping angle 15-20°), making the interlacing points elastic locking nodes. This allows the wrapped structure to stretch and release elasticity during stretching, and the wrapping force to quickly reset the yarns during rebound. In this invention, the interlacing point density of warp and weft yarns is 380-420 points / 10cm². This high density of interlacing points can evenly distribute frictional stress and avoid concentrated local wear.

[0023] Step 5: A coating precursor solution is formed by combining polyurethane urea elastomer and silicon carbide@graphene core-shell nanoparticles. The fabric preform is immersed in the coating precursor solution, pre-baked, and cured in situ, allowing the coating precursor solution to form a 5-10 μm thick network cross-linked coating on the surface of the fabric preform, resulting in a highly elastic and wear-resistant fabric. Specifically, the silicon carbide@graphene core-shell nanoparticles have a core diameter of 80 nm and a shell thickness of 15 nm. First, the silicon carbide@graphene core-shell nanoparticles are prepared into a dispersion. Then, the polyurethane urea elastomer is transferred to a constant-temperature reactor, maintained at 45°C, and stirred at 600 r / min. The dispersion is slowly added in three portions, with the speed increased to 1000 r / min and stirred for 20 min after each addition. Next, a polycarboxylate dispersant is added and stirring continues for 30 min. Finally, a polyether-modified dispersant is added. The polysiloxane leveling agent was stirred for another 30 minutes to adjust the viscosity of the system to 1100 mPa·s. An ethanol / deionized water mixed solvent was added to control the precursor solid content at 13%, resulting in a coating precursor solution. The fabric preform was immersed in the coating precursor solution for 15 minutes and then pre-dried at 75℃ for 10 minutes. In-situ curing was then performed at 130℃ for 25 minutes. Finally, after cooling to room temperature, the fabric was finished to obtain a high-elasticity, abrasion-resistant fabric. In this step, the coating precursor solution forms a 5-10 μm thick network cross-linked coating on the surface of the fabric preform. This network cross-linked coating not only forms a wear-resistant protective layer on the fabric surface but also retains the fabric's breathability. Simultaneously, the addition of polyurethane urea elastomer gives the coating elasticity that matches the fabric, preventing coating cracking.

[0024] The performance of the high-elasticity abrasion-resistant fabric prepared in the above embodiments was tested, and the results are shown in Table 1 below: Table 1

[0025] The high-elasticity abrasion-resistant fabric prepared by the three-dimensional cross-knitting process in this invention has the advantages shown in Table 2 below compared with the high-elasticity abrasion-resistant fabric prepared by the traditional two-dimensional plain weave: Table 2

[0026] This invention produces composite elastic fibers that combine high elasticity and basic wear resistance by using polyether ester as a base material and preparing them through graphene grafting modification and UHMWPE microfiber blending and spinning. Aminated graphene is grafted onto the polyether ester molecular chain, and the graphene sheets are covalently bonded to the polyether ester, which solves the compatibility problem between graphene and polymer. Furthermore, the high hardness and thermal conductivity of graphene can be used to improve the surface wear resistance and thermal stability of the composite elastic fibers. During the spinning process, UHMWPE microfibers can form a rigid support skeleton, which does not affect the elastic recovery of polyether ester and can disperse frictional stress, avoiding excessive local wear of the composite elastic fibers. This invention uses composite elastic fibers twisted with nylon 66 filaments as warp yarns and UHMWPE filaments as core yarns wrapped with composite elastic fibers as weft yarns. The warp and weft yarns are woven using a three-dimensional interlacing weave process, and the interlacing points of the warp and weft yarns are controlled to form a "plum blossom" locking structure, which can further enhance the synergy between the elasticity and abrasion resistance of the fabric. The "plum blossom" locking structure allows the coils to stretch and release elasticity when stretched, and the coils to quickly return to their original position when rebounding. At the same time, the dense distribution of interlacing points can disperse external frictional forces and avoid localized wear. This invention also uses polyurethane urea elastomer and silicon carbide@graphene core-shell nanoparticles to form a coating precursor solution. The fabric blank is immersed in the coating precursor solution, pre-dried, and cured in situ. This forms an abrasion-resistant elastic coating on the fabric surface that is tightly bonded to the fibers and structure, achieving a secondary enhancement of elasticity and abrasion resistance.

[0027] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method of making a high-elasticity, abrasion-resistant fabric, characterized by, The method comprises the following steps: Step 1: melt blending and spinning of polyether ester chips, aminated graphene, UHMWPE microfiber and maleic anhydride grafted polyolefin compatibilizer to obtain composite elastic fiber; Step 2: twisting the composite elastic fiber and the polyamide 66 filament according to a ratio of (6-7):(3-4) to form a twisted structure as warp yarn; Step 3: wrapping the UHMWPE filament as core yarn with the composite elastic fiber as wrapping yarn to form a core-in-sheath structure as weft yarn; Step 4: weaving the warp yarn and the weft yarn by using a three-dimensional interweaving process, and controlling the interweaving points of the warp yarn and the weft yarn to form a "plum blossom" locking structure to obtain a fabric roughcast; Step 5: compounding polyurethane urea elastomer with silicon carbide@graphene core-shell nanoparticles to form a coating precursor solution, immersing the fabric roughcast in the coating precursor solution, pre-drying, in-situ curing, and allowing the coating precursor solution to form a reticular crosslinked coating with a thickness of 5-10 μm on the surface of the fabric roughcast to obtain a high-elasticity wear-resistant fabric.

2. A method of making a high-elasticity, abrasion-resistant fabric according to claim 1, characterized in that: In the step 1, the aminated graphene accounts for 2-5 wt%, the UHMWPE microfiber accounts for 5-10 wt%, the compatibilizer accounts for 3-5 wt%, and the rest is polyether ester chips, and the UHMWPE microfiber has a diameter of 50-100 nm and a length of 1-3 μm.

3. A method of making a high stretch, abrasion resistant fabric according to claim 2, characterized in that: In the step 1, the polyether ester chips, the aminated graphene, the UHMWPE microfiber and the maleic anhydride grafted polyolefin compatibilizer are melt blended by a double-screw extruder at 220-240°C, extruded and granulated to obtain a composite master batch, and then the composite master batch is sent to a spinning machine, the spinning hole diameter is set to 0.1-0.2 mm, the spinning temperature is set to 230-250°C, the cooling air speed is set to 0.8-1.2 m / s, and the draw ratio is set to 3-4 times to obtain the composite elastic fiber.

4. The method of claim 1, wherein: In the step 2, the twist degree is controlled to be 800-1000 twists per meter when the composite elastic fiber is twisted with the polyamide 66 filament.

5. A method of making a high stretch, abrasion resistant fabric according to claim 4, characterized in that: In the step 3, the wrapping twist degree is 600-800 twists per meter when the UHMWPE filament is used as core yarn and the composite elastic fiber is used as wrapping yarn for wrapping.

6. A method of making a high stretch, abrasion resistant fabric according to claim 5, wherein: In the step 4, the warp density is 280-320 per 10 cm and the weft density is 230-270 per 10 cm when the warp yarn and the weft yarn are woven by using a three-dimensional interweaving process.

7. A method of making a high stretch, abrasion resistant fabric according to claim 6, wherein: In the step 4, the density of the interweaving points of the warp yarn and the weft yarn in the fabric roughcast to form the "plum blossom" locking structure is 1.5-2 times the density of plain weave.

8. The method of claim 1, wherein: In the step 5, the core diameter of the silicon carbide@graphene core-shell nanoparticles is 50-100 nm, and the shell thickness is 10-20 nm.

9. A method of making a high stretch, abrasion resistant fabric according to claim 8, characterized in that: In the step five, when the polyurethane urea elastomer is compounded with the silicon carbide@graphene core-shell nanoparticles to form the coating precursor solution, first, the silicon carbide@graphene core-shell nanoparticles are prepared into a dispersion liquid, then the polyurethane urea elastomer is transferred to a constant temperature reaction kettle, the temperature is maintained at 40-45℃, the stirring is started at a speed of 500-700 r / min, the dispersion liquid is slowly added in three times, the speed is increased and stirring is conducted for 20 min after each addition, then the polycarboxylate dispersant is added and stirring is continued, finally the polyether modified polysiloxane leveling agent is added and stirring is continued for 30 min, the viscosity of the system is adjusted to 1000-1200 mPa・s, the mixed solvent of ethanol / deionized water is supplemented, the solid content of the precursor is controlled to be 12%-14%, and the coating precursor solution is obtained.

10. A method of making a high stretch, abrasion resistant fabric according to claim 9, characterized in that: In the step five, after the fabric rough blank is immersed in the coating precursor solution, the pre-baking temperature is 70-90℃, the pre-baking time is 8-12 min, the in-situ curing temperature is 120-140℃, and the in-situ curing time is 20-30 min.